2009
DOI: 10.1007/s00244-009-9352-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Concentrations in Raillietina micracantha in Comparison to Its Definitive Host, the Feral Pigeon Columba livia in Santa Cruz de Tenerife (Canary Archipelago, Spain)

Abstract: The use of systems involving bird parasites as bioindicators of environmental pollution has been scarcely studied in comparison to other models involving fish and rodent parasites, which have been demonstrated as particularly adequate due to their bioaccumulation capacities. The present study evaluated the accumulation of nine trace elements in the cestode Raillietina micracantha and in its host Columba livia collected from the densely populated city of Santa Cruz de Tenerife (Canary Islands, Spain). Samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(41 reference statements)
3
10
5
Order By: Relevance
“…This research showed that the intestine, kidney, gizzard, and liver have almost higher metal concentrations than the muscle. Such pattern has been observed in a number of other studies, covering a wide spectrum of pigeon (Torres et al 2010;Nam et al 2006;Schilderman et al 1997). In Bangladesh, the recent average per capita consumption of fish/meat was 21 g/person/day for males and females of all ages (Begum et al 2005).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…This research showed that the intestine, kidney, gizzard, and liver have almost higher metal concentrations than the muscle. Such pattern has been observed in a number of other studies, covering a wide spectrum of pigeon (Torres et al 2010;Nam et al 2006;Schilderman et al 1997). In Bangladesh, the recent average per capita consumption of fish/meat was 21 g/person/day for males and females of all ages (Begum et al 2005).…”
Section: Resultssupporting
confidence: 70%
“…The same distribution pattern of Cd was recorded (highest levels in the liver, lowest in the muscle) in other pigeons in spain (Torres et al 2010). The maximum admissible value for pigeon is 0.05 µg/g wet weight (EU Commission 2001).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations